To evaluate the expression \( 1 \frac{3}{8} - \frac{5}{8} - 3 \frac{1}{8} \), we first convert the mixed numbers into improper fractions.
-
Convert \( 1 \frac{3}{8} \): \[ 1 \frac{3}{8} = \frac{8 \cdot 1 + 3}{8} = \frac{8 + 3}{8} = \frac{11}{8} \]
-
Convert \( 3 \frac{1}{8} \): \[ 3 \frac{1}{8} = \frac{8 \cdot 3 + 1}{8} = \frac{24 + 1}{8} = \frac{25}{8} \]
Now we can rewrite the expression using improper fractions: \[ \frac{11}{8} - \frac{5}{8} - \frac{25}{8} \]
Next, we will combine all three fractions: \[ \frac{11 - 5 - 25}{8} = \frac{11 - 30}{8} = \frac{-19}{8} \]
Now, we can convert \(\frac{-19}{8}\) back into a mixed number: \[ -19 \div 8 = -2 \quad \text{(with a remainder of 3)} \] So, \[ -19 = -2 \cdot 8 + 3 \implies \frac{-19}{8} = -2 \frac{3}{8} \]
Therefore, the evaluated expression is: \[ -2 \frac{3}{8} \]
The correct answer is: D. -2 3/8